Caractéristiques de la leucémie lymphoïde chronique au Togo - Padaro, Essohana (Pan Afr Med J, 2019)
The epidemiological, clinical and biological characteristics of chronic lymphocytic leukemia (CLL) are little studied in Togo. The purpose of this study was to describe these characteristics at the time of diagnosis. We conducted a retrospective and descriptive study of patients diagnosed at the University Hospital Campus from January 1999 to December 2018. Over the past two decades, 87 patients were seen for CLL (20% of patients with hematological malignancies) with an annual prevalence of 4.35 new cases. The average age of patients was 61 +/- 12,48 years (ranging from 17-85 years); 55 women and 32 men (sex ratio M/F 0.58) were enrolled. Clinically, 16 patients (18%) had no tumor syndrome, 33 patients (38%) had lymphadenopathy, 62 patients (71%) splenomegaly and 23 patients (26%) hepatomegaly. Biologically, the mean blood and medullary lymphocyte count was 87188/mm(3) (ranging from 7000-481780/mm(3)) and 75.75% +/- 12,88 (ranging from 44,5-96,5%) respectively; 65 patients (75%) had haemoglobin less than 10g/dl and 20 patients (23%) had platelet count below 100000/mm(3). At the time of diagnosis, 67 patients (77%) had Binet stage C, 7 patients (8%) stage B and 13 patients (15%) stage A. The study of biological prognostics factors showed that 66% of cases had β2-microglobulin level higher than normal and 95% of cases had LDH higher than normal. CLL is a reality in Togo with a predominance of women and an average age of 61 years. Most patients are seen at Binet stage C and their assessment has revealed huge tumor mass with increased LDH and β2-microglobulin. The current follow-up of these patients will enable us to assess their overall survival.